Autoconditioning factor relieves ethanol-induced growth inhibition of Saccharomyces cerevisiae. - Walker-Caprioglio, H M (1987)
Viable Saccharomyces cerevisiae suspended in medium containing growth-inhibiting concentrations of ethanol produce a metabolite that relieves growth inhibition. This autoconditioning of the medium by yeasts is due to the formation of small amounts (0.01%, vol/vol) of acetaldehyde. The effect is duplicated precisely in fresh medium by the addition of acetaldehyde. Acetaldehyde does not increase the yield of or accelerate ethanol production by the organism. Ethanol-induced modifications of membrane order in the plasma membranes, as measured by steady-state fluorescence anisotropy of 1,6-diphenyl-1,3,5-hexatriene, were not resolved by exogenously added acetaldehyde.